Hydrodesulfurization catalyst, method for preparing the same, and use thereof

CN117861717BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211245598.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2026-10-16
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

[0012]本发明的目的是为了克服现有技术存在的加氢脱硫催化剂脱硫活性差和直接脱硫选择性差的问题,提供一种加氢脱硫催化剂及其制备方法与应用的,该催化剂具有脱硫活性高、直接脱硫选择性更高以及反应氢耗低的优点

Benefits of technology

[0025]The inventors discovered that introducing EWT-structured molecular sieves with ultra-large pores facilitates contact between reactant molecules and more acid centers on the sieve surface, promoting reactant molecule transformation. Introducing rare earth elements helps increase the total acid content and improve the strong B/L acid ratio while maintaining the stability of the molecular sieve framework, thus promoting the desulfurization reaction. A hydrodesulfurization catalyst was prepared by combining rare earth-modified EWT-structured molecular sieves with an inorganic heat-resistant matrix as a support, and then loading active components and optional additives. This hydrodesulfurization catalyst exhibits high direct desulfurization activity, significantly improved selectivity in the direct desulfurization pathway, and reduced hydrogen consumption during the reaction process, making it promising for application in ultra-deep desulfurization reactions of diesel fuel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003886451220000071
    Figure BDA0003886451220000071
  • Figure BDA0003886451220000101
    Figure BDA0003886451220000101
  • Figure BDA0003886451220000102
    Figure BDA0003886451220000102
Patent Text Reader

Abstract

The present application relates to the technical field of hydrodesulfurization, and discloses a hydrodesulfurization catalyst and a preparation method and application thereof.A hydrodesulfurization catalyst, wherein the catalyst comprises a carrier, an active component supported on the carrier, and an optional auxiliary agent; the carrier comprises an inorganic heat-resistant matrix and a rare earth modified EWT structure molecular sieve; the content of the rare earth element in the rare earth modified EWT structure molecular sieve is 0.05-2.5 wt% based on the total amount of the rare earth modified EWT structure molecular sieve; the B acid / L acid content ratio of the rare earth modified EWT structure molecular sieve is 0.1-1; the active component comprises at least one of a group VIII metal element and at least one of a group VIB metal element; and the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.The catalyst can be used in a hydrodesulfurization reaction of a raw material containing a sterically hindered molecule, and has high desulfurization activity, high direct desulfurization selectivity and low hydrogen consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of hydrodesulfurization, specifically to a hydrodesulfurization catalyst, its preparation method, and its application. Background Technology

[0002] With increasingly stringent environmental regulations on air pollutant emissions in recent years, countries worldwide have established stricter fuel standards. Simultaneously, petroleum resources are becoming heavier and of lower quality. Therefore, significantly reducing the impurity content in fuels and improving the quality of gasoline and diesel products has become a pressing issue for major oil refineries. Sulfur in diesel fuel has a significant impact on vehicle exhaust emissions, thus requiring strict limits on its sulfur content. Hydrogenation technology is one of the main technologies for producing ultra-low sulfur diesel, characterized by high desulfurization efficiency, low operating costs, and wide applicability. The core of this technology is the hydrogenation catalyst.

[0003] Hydrotreating catalysts typically use alumina-supported molybdenum and / or tungsten transition metal sulfide catalysts with cobalt and / or nickel as promoters. These catalysts are highly efficient at removing sulfur-containing compounds such as benzothiophenes and dibenzothiophenes during deep hydrodesulfurization of diesel fuel. However, for alkyl-substituted dibenzothiophene compounds, especially those with alkyl substituents at the 4 and 6 positions (such as 4,6-dimethyldibenzothiophene), the steric hindrance effect introduced by the alkyl substitution significantly reduces the reactivity of the sulfides, making ultra-deep desulfurization of diesel fuel difficult to achieve.

[0004] Dibenzothiophene compounds undergo desulfurization primarily through two reaction pathways: a hydrogenation pathway, where the sulfide interacts with the catalyst via π-type adsorption, saturating one aromatic ring with hydrogen before the C-S bond breaks under hydrogen ionization; and a direct desulfurization pathway, where the sulfide interacts with the catalyst via σ-type adsorption, directly breaking the C-S bond of the thiophene ring to remove sulfur. However, for alkyl-substituted dibenzothiophene compounds, the steric hindrance effect of the alkyl substitution significantly inhibits σ-type adsorption of the sulfide, while having a smaller impact on π-type adsorption. This results in a significant reduction in the direct desulfurization activity of the catalyst and a decrease in the overall hydrogenation desulfurization activity.

[0005] Currently, industrial ultra-deep desulfurization catalysts primarily utilize a hydrogenation pathway—specifically, hydrogen saturation of the aromatic ring followed by desulfurization—to convert 4,6-dimethyldibenzothiophene. However, this pathway consumes a significant amount of hydrogen. To improve the desulfurization rate of the catalysts while reducing hydrogen consumption, researchers have proposed various novel methods for catalyst preparation and modification.

[0006] Patent application CN103143365A discloses a hydrogenation catalyst in which molybdenum and cobalt or nickel are supported in a stepwise manner on a γ-Al₂O₃ or TiO₂-γ-Al₂O₃ support. Molybdenum is supported using sodium molybdate as a raw material, hydrochloric acid or nitric acid solution as an acidifying agent, and a single-chain organic quaternary ammonium salt as a precipitant. The molybdenum-based single-component supported catalyst is prepared through aqueous diffusion, channel deposition technology, and processes including filtration, washing, drying, and calcination. Subsequently, cobalt or nickel is loaded onto the support via a room-temperature, equal-volume impregnation method. This method effectively improves the loading of the active components and their dispersion in the channels, thus enhancing the catalyst's hydrodesulfurization activity; however, the preparation process is relatively complex.

[0007] Patent application CN107694583A discloses an ultra-deep desulfurization catalyst. This catalyst uses a porous carbon material as a support, which is oxidized and then dispersed in an ammonia solution containing nickel inorganic salts to support nickel. Subsequently, a triphenylphosphine cyclohexane solution is passed through in a hydrogen atmosphere, followed by calcination to obtain a porous carbon catalyst with highly dispersed Ni₂P. The Ni₂P-supported porous carbon catalyst prepared by this method has more active sites and improved hydrodesulfurization activity, but this improvement mainly comes from its hydrogenation activity. Furthermore, compared with conventional sulfide catalysts, its stability is relatively poor.

[0008] Patent application CN1184843A discloses a diesel hydroconversion catalyst. The catalyst support is obtained by mixing, molding, and calcining 40-80 wt% alumina, 0-20 wt% amorphous silica-alumina, and 5-30 wt% Y-type molecular sieve. The Y-type molecular sieve used has a pore volume of 0.4-0.52 mL / g and a specific surface area of ​​750-900 m². 2 The catalyst has a SiO2 / Al2O3 ratio of 7-15 and its active metal components are nickel and tungsten. It exhibits high hydrodesulfurization activity, but the diesel yield decreases while the cetane number shows minimal change.

[0009] Patent application CN105772109A discloses a hydrodesulfurization catalyst. The catalyst support is obtained by mixing, molding, and calcining 50-98 wt% alumina and 1-30 wt% zirconium-modified high-silicon-to-alumina ratio Y-type molecular sieves. The zirconium oxide content is 0.1-6 wt% of the mass of the zirconium-modified Y-type molecular sieve. The hydrodesulfurization catalyst prepared with this support exhibits high desulfurization activity and a relatively high diesel yield. However, the catalyst primarily removes recalcitrant sulfides via a hydrogenation pathway, resulting in high hydrogen consumption during the reaction process.

[0010] Patent application CN109422627A discloses a method for using a catalyst containing an EWT-structured molecular sieve to prepare tert-butylglycerol ether via glycerol etherification. The EWT-structured molecular sieve used has a three-dimensional ten-membered ring and a twenty-one-membered ring structure. Its large pore size and abundant pore structure facilitate the diffusion of reactant molecules, improving the reactivity of the glycerol etherification catalyst and the selectivity of etherified glycerol. Adding an EWT-structured molecular sieve to the catalyst not only promotes the diffusion of large molecular reactants but also improves the utilization rate of the acidic centers of the molecular sieve.

[0011] Existing hydrodesulfurization catalysts can meet the requirements of some ultra-deep desulfurization reactions. However, due to the low selectivity of direct desulfurization of the catalysts, the removal of difficult-to-desulfurize compounds is mainly achieved through the hydrogenation pathway, resulting in high hydrogen consumption during the reaction process. Summary of the Invention

[0012] The purpose of this invention is to overcome the problems of poor desulfurization activity and poor direct desulfurization selectivity of existing hydrodesulfurization catalysts, and to provide a hydrodesulfurization catalyst, its preparation method and application. This catalyst has the advantages of high desulfurization activity, higher direct desulfurization selectivity and low hydrogen consumption.

[0013] To achieve the above objectives, a first aspect of the present invention provides a hydrodesulfurization catalyst, wherein the catalyst comprises a support, an active component supported on the support, and optional auxiliary agents; wherein the support comprises an inorganic heat-resistant matrix and a rare earth-modified EWT structured molecular sieve; wherein, based on the total amount of the rare earth-modified EWT structured molecular sieve, the content of rare earth elements in the rare earth-modified EWT structured molecular sieve is 0.05-2.5% by weight; wherein, based on the total amount of the rare earth-modified EWT structured molecular sieve, the total acidity is 0.25-0.5 mmol NH3·g. -1 The rare earth modified EWT structured molecular sieve has a Brønsted acid / Lønsted acid content ratio of 0.1-1; the active component is selected from at least one group VIII metal element and at least one group VIB metal element; and the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.

[0014] Preferably, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is ​​20-80% by weight, the content of the rare earth modified EWT structure molecular sieve is 5-40% by weight, the content of the Group VIII metal element (calculated as oxide) is 2-10% by weight, the content of the Group VIB metal element (calculated as oxide) is 10-40% by weight, and the content of the additive (calculated as oxide) is 0-8% by weight.

[0015] Preferably, the preparation method of the rare earth modified EWT structure molecular sieve includes: introducing rare earth elements into the EWT structure molecular sieve for modification treatment by at least one of ion exchange, impregnation and precipitation methods.

[0016] Preferably, the solution containing rare earth element precursors is ion exchanged with EWT structured molecular sieves by ion exchange, followed by drying and calcination.

[0017] A second aspect of the present invention provides a method for preparing a hydrodesulfurization catalyst, wherein the method includes:

[0018] (1) An inorganic heat-resistant matrix and / or its precursor are mixed with modified EWT structural molecules, molded, and calcined to obtain a carrier;

[0019] (2) The carrier from step (1) is impregnated with a solution containing the precursor of the active component and then dried and calcined;

[0020] The method also includes optionally introducing an adjuvant in step (1) and / or step (2);

[0021] The active component is selected from at least one group VIII metal element and at least one group VIB metal element; the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.

[0022] Based on the total amount of rare earth modified EWT structured molecular sieve, the content of rare earth elements in the rare earth modified EWT structured molecular sieve is 0.05-2.5% by weight.

[0023] In the rare earth-modified EWT structured molecular sieve, based on the total amount of rare earth-modified EWT structured molecular sieve, the total acid content is 0.25-0.5 mmol NH3·g. -1 Preferably, the concentration is 0.25-0.45 mmol NH3·g -1 The ratio of Brønsted acid to Lønsted acid in the rare earth modified EWT molecular sieve is 0.1-1, preferably 0.15-0.6.

[0024] The third aspect of this invention provides the application of the hydrodesulfurization catalyst described in the first aspect in a hydrodesulfurization reaction containing sterically hindered molecular feedstock.

[0025] The inventors discovered that introducing EWT-structured molecular sieves with ultra-large pores facilitates contact between reactant molecules and more acid centers on the sieve surface, promoting reactant molecule transformation. Introducing rare earth elements helps increase the total acid content and improve the strong B / L acid ratio while maintaining the stability of the molecular sieve framework, thus promoting the desulfurization reaction. A hydrodesulfurization catalyst was prepared by combining rare earth-modified EWT-structured molecular sieves with an inorganic heat-resistant matrix as a support, and then loading active components and optional additives. This hydrodesulfurization catalyst exhibits high direct desulfurization activity, significantly improved selectivity in the direct desulfurization pathway, and reduced hydrogen consumption during the reaction process, making it promising for application in ultra-deep desulfurization reactions of diesel fuel. Detailed Implementation

[0026] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0027] The first aspect of this invention provides a hydrodesulfurization catalyst, wherein the catalyst comprises a support, an active component supported on the support, and optional auxiliary agents; wherein the support comprises an inorganic heat-resistant matrix and a rare earth-modified EWT structured molecular sieve; wherein, based on the total amount of the rare earth-modified EWT structured molecular sieve, the content of rare earth elements in the rare earth-modified EWT structured molecular sieve is 0.05-2.5% by weight; wherein, based on the total amount of the rare earth-modified EWT structured molecular sieve, the total acidity is 0.25-0.5 mmol NH3·g. -1 The rare earth modified EWT structured molecular sieve has a Brønsted acid / Lønsted acid content ratio of 0.1-1; the active component is selected from at least one group VIII metal element and at least one group VIB metal element; and the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.

[0028] This invention introduces rare earth elements to prepare rare earth-modified EWT structured molecular sieves, which increases the total acid content and the ratio of Brønsted acid to Lønnel acid in the EWT structured molecular sieves. This allows the rare earth-modified EWT structured molecular sieves to be combined with an inorganic heat-resistant matrix to form a support, which is then loaded with active components and optional additives to prepare a hydrodesulfurization catalyst. This catalyst exhibits significantly improved selectivity and activity for the direct desulfurization pathway, while reducing hydrogen consumption, making it a promising candidate for deep desulfurization of diesel fuel.

[0029] In this invention, there are no specific limitations on the content of each substance in the catalyst. Preferably, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is ​​20-80% by weight, the content of the rare earth modified EWT structured molecular sieve is 5-40% by weight, the content of the Group VIII metal element (calculated as oxide) is 2-10% by weight, the content of the Group VIB metal element (calculated as oxide) is 10-40% by weight, and the content of the additive (calculated as oxide) is 0-8% by weight; more preferably, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is ​​30-70% by weight, the content of the rare earth modified EWT structured molecular sieve is 5-30% by weight, the content of the Group VIII metal element (calculated as oxide) is 2-8% by weight, the content of the Group VIB metal element (calculated as oxide) is 10-30% by weight, and the content of the additive (calculated as oxide) is 0-7% by weight. This preferred embodiment facilitates the balancing and control of the activity of each reaction pathway in the hydrodesulfurization of the catalyst, improves the selectivity and activity of the desulfurization reaction, and reduces the occurrence of side reactions.

[0030] In this invention, all inorganic heat-resistant matrices conventionally defined in the art are applicable, and those skilled in the art can select them according to specific needs. Preferably, the inorganic heat-resistant matrix is ​​selected from at least one of alumina, silicon oxide, titanium oxide, magnesium oxide, alumina-magnesium oxide, silicon oxide-alumina, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thorium oxide, silicon oxide-beryllium oxide, silicon oxide-titanium oxide, silicon oxide-alumina-thorium oxide, silicon oxide-alumina-titanium oxide, silicon oxide-alumina-magnesium oxide, silicon oxide-alumina-zirconium oxide, phosphorus oxide-alumina, phosphorus oxide-alumina-alumina, and natural zeolite, and is more preferably alumina.

[0031] In a preferred embodiment, the alumina is selected from at least one of the following: alumina with X-ray diffraction characteristics of γ, η, θ, δ, and χ, and amorphous; aluminum hydroxide; hydrated alumina; and amorphous aluminum hydroxide. Alumina can be obtained commercially or prepared using existing methods.

[0032] Using the above-mentioned preferred alumina can provide the catalyst with a large specific surface area and pore volume, promote the dispersion of active metals on alumina, and improve the activity and stability of the catalyst.

[0033] In this invention, there is no particular limitation on the type of EWT structured molecular sieve. Preferably, the rare earth modified EWT structured molecular sieve is EMM-23.

[0034] In this invention, there is no specific limitation on the source of EWT structure molecular sieve. It can be obtained from commercial products or by self-production. For example, the EWT structure molecular sieve in this invention was prepared by the Petroleum and Chemical Research Institute with reference to the method in patent application CN108238610A. Specifically, the EWT structure molecular sieve was prepared by the following method: (1) Preparing an initial gel mixture containing silicon source, aluminum source, template agent, water and alkali source, wherein the silicon source is SiO2 and the aluminum source is Al2O3, and the molar ratio of silicon source, aluminum source, template agent, water and alkali metal hydroxide is 1:0.005-1:0.01-0.5:5-50:0-1;

[0035] (2) Crystallize the initial gel mixture in step (1) at a temperature of 80-200℃ for 1-8 days and at a pressure of self-generated pressure during the crystallization process.

[0036] (3) The molecular sieve slurry after crystallization is subjected to ammonium exchange, filtration, washing, drying and calcination to obtain the EWT structured molecular sieve.

[0037] In this invention, preferably, in the method for preparing the silica-alumina molecular sieve, the template agent is selected from compounds represented by formula (I).

[0038]

[0039] Wherein, groups R1 and R2 may be the same as or different from each other; preferably, R1 and R2 are each independently selected from C. 3-12 Straight-chain or branched alkylene groups, preferably each independently selected from C10. 3-12 Straight-chain alkylene groups, particularly preferably one selected from C10. 3-12 A straight-chain alkylene group, another selected from C 4-6 Straight-chain alkylene; multiple groups R may be the same as or different from each other, preferably, each of the multiple groups R is independently selected from C 1-4 Straight-chain or branched alkyl groups, preferably each independently selected from methyl and ethyl, more preferably both being methyl; X is -OH.

[0040] In this invention, the filtration, washing, and drying processes in the preparation method of the EWT structured molecular sieve can be performed in any manner conventionally known in the art. Specifically, the filtration may be, for example, a reaction mixture obtained by vacuum filtration. The washing may be performed, for example, with deionized water until the pH of the filtrate reaches 7-9. The drying conditions are: temperature 80-120°C, time 4-15 hours. This invention may also include a calcination step; the calcination can be performed in any manner conventionally known in the art, with a calcination temperature of 350-750°C, a calcination time of 2-8 hours, and a calcination atmosphere generally consisting of air or oxygen.

[0041] In this invention, the preparation method of the EWT structured molecular sieve does not impose any particular limitation on the silicon source; any conventionally known silicon source used for preparing molecular sieves can be used in this invention. Preferably, the silicon source is selected from at least one of silica sol, solid silica gel, tetraethyl orthosilicate, fumed silica, and water glass.

[0042] In this invention, the method for preparing the EWT structured molecular sieve does not impose any particular limitation on the aluminum source; any aluminum source conventionally known for preparing molecular sieves can be used in this invention. Preferably, the aluminum source is selected from at least one of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum hydroxide, sodium aluminate, and aluminum sol.

[0043] In this invention, the preparation method of the EWT structured molecular sieve does not have any particular limitations on the alkali source. Preferably, the alkali source is sodium hydroxide and / or potassium hydroxide.

[0044] The EWT structured molecular sieve obtained by this preparation method has a high acid content, which is beneficial for expanding its application in acid-catalyzed reactions; in addition, the molecular sieve crystal contains abundant mesoporous structures, which greatly promotes the diffusion of reactant molecules in the molecular sieve channels.

[0045] In this invention, rare earth elements are introduced to modify the EWT structure molecular sieve, resulting in a rare earth-modified EWT structure molecular sieve. All rare earth elements conventionally defined in the art are applicable to this invention. Preferably, the rare earth element is selected from at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium, and more preferably lanthanum and / or cerium. This preferred embodiment helps maintain or improve the structural stability of the molecular sieve and increases the total acidity of the molecular sieve.

[0046] In a preferred embodiment, based on the total amount of rare earth-modified EWT structured molecular sieve, the content of the EWT structured molecular sieve is 97.95-99.9% by weight, the content of lanthanum is 0.05-1.25% by weight, and the content of cerium is 0.05-1.25% by weight. More preferably, based on the total amount of rare earth-modified EWT structured molecular sieve, the content of the EWT structured molecular sieve is 98-99.9% by weight, the content of lanthanum is 0.05-1% by weight, and the content of cerium is 0.05-1% by weight. This preferred embodiment helps to increase the total acid content and improve the strong B / L acid ratio while maintaining the stability of the molecular sieve framework.

[0047] According to a preferred embodiment of the present invention, the total acid content of the rare earth modified EWT structured molecular sieve is 0.25-0.45 mmol NH3·g, based on the total amount of rare earth modified EWT structured molecular sieve. -1Further preferably, it is 0.25-0.4 mmol NH3·g -1 This preferred embodiment can increase the total acid content of the molecular sieve while improving the strong B / L acid ratio, thereby enhancing the selection of the target reaction pathway.

[0048] According to a preferred embodiment of the present invention, the Brønsted acid / Lønsted acid content ratio of the rare earth modified EWT structured molecular sieve is 0.15-0.6, more preferably 0.15-0.55. This preferred embodiment helps to increase the strong Brønsted acid / Lønsted acid ratio, and the strong Brønsted acid centers can promote the desulfurization reaction.

[0049] In this invention, there are no particular limitations on the characteristic parameters of the rare earth-modified EWT structured molecular sieve. Preferably, the silicon-to-aluminum atomic ratio of the rare earth-modified EWT structured molecular sieve is 10-50, and the framework aluminum / non-framework aluminum ratio is 1-6. More preferably, the silicon-to-aluminum atomic ratio is 30-50, and the framework aluminum / non-framework aluminum ratio is 1-3. This preferred embodiment helps to increase the total acid content while maintaining the stability of the molecular sieve framework, and also simplifies the molecular sieve synthesis process.

[0050] In this invention, the total acidity of the rare earth modified EWT structure molecular sieve was determined by the NH3-TPD method, see "Research Methods for Solid Catalysts, Petrochemical Technology, 30(12), 2001: 952".

[0051] In this invention, the ratio of Brønsted acid content to Lewis acid content in the rare earth-modified EWT structured molecular sieve was determined using a Bio-Rad IFS-3000 infrared spectrometer. The specific method involved grinding the molecular sieve sample and pressing it to approximately 10 mg / cm³. 2 The self-supporting sheet was placed in the in-situ cell of an infrared spectrometer and subjected to 350℃ and 10... -3 Surface purification was performed under vacuum of Pa for 2 hours. After cooling to room temperature, pyridine saturated vapor was introduced. After adsorption equilibrium for 15 minutes, desorption was carried out under vacuum at 200℃ and 350℃ for 30 minutes respectively. After cooling to room temperature, the vibrational spectra of adsorbed pyridine were measured, and the Brønsted acid (B) and Lewis acid (L) values ​​of the catalyst were determined under the conditions of 200℃ and 300℃. The scanning range was 1400 cm⁻¹. -1 -1700cm -1 1540±5cm -1 The Brønsted acid content is defined as the ratio of the infrared absorbance of a spectral band to the weight and area of ​​the sample. (Using 1450±5 cm⁻¹) -1 The ratio of the infrared absorbance of a spectral band to the weight and area of ​​the sample sheet defines its L acid content, and the ratio of Benz acid content to L acid content is defined as the ratio of Benz acid content to L acid content in the zeolite molecular sieve. The corresponding Benz acid and L acid contents are calculated using the following formulas.

[0052]

[0053]

[0054] In this invention, the silicon-to-aluminum atomic ratio is determined using X-ray fluorescence spectrometry. Specifically, it is calculated from the content of silicon oxide and aluminum oxide, which are determined according to the standard method of GB / T 30905-2014.

[0055] In this invention, the ratio of skeletal aluminum to non-skeletal aluminum is measured using a Bruker Avance III 500MHz nuclear magnetic resonance spectrometer. After peak fitting of the resonance peak spectrum, the area of ​​each peak is calculated using the integration method. The peaks at 60±1ppm and 0±1ppm correspond to skeletal aluminum and non-skeletal aluminum, respectively. The ratio of the peak areas of skeletal aluminum and non-skeletal aluminum is the ratio of skeletal aluminum to non-skeletal aluminum.

[0056] In this invention, there are no particular limitations on the structural parameters of the rare earth-modified EWT molecular sieve. Preferably, the specific surface area of ​​the rare earth-modified EWT molecular sieve is 500-650 m². 2 / g, pore volume 0.25-0.35cm³ 3 / g.

[0057] In this invention, the specific surface area of ​​the rare earth modified EWT structure molecular sieve is measured using the nitrogen adsorption BET specific surface area method; the pore volume is determined using the standard method of GB / T 5816-1995.

[0058] According to a preferred embodiment of the present invention, the method for preparing rare earth modified EWT structured molecular sieve is as follows: rare earth elements are introduced into the EWT structured molecular sieve for modification treatment by means of ion exchange, impregnation or precipitation.

[0059] According to a particularly preferred embodiment of the present invention, an ion exchange method is used to ion exchange a solution containing a rare earth element precursor with an EWT structured molecular sieve, followed by drying and calcination. Specifically, based on the dry weight of ammonium or sodium type EWT structured molecular sieve powder, a rare earth element precursor solution is prepared at a dry weight to solution mass ratio of 1:5-1:20. The solution is then mixed evenly with the molecular sieve powder and stirred and impregnated in a heated stirrer at 60-120°C for 2-8 hours. After washing and filtration, the mixture is dried and calcined to prepare a rare earth modified EWT structured molecular sieve.

[0060] In this invention, the dry basis weight is the weight of the molecular sieve after calcination at 800°C for 1 hour.

[0061] In this invention, there is no specific limitation on the type of rare earth element precursor; all rare earth element precursors conventionally defined in the art are applicable. Preferably, the rare earth element precursor is selected from at least one of nitrates, sulfates, chlorides, phosphates, and carbonates; more preferably, the rare earth element precursor is selected from at least one of cerium nitrate, cerium sulfate, lanthanum nitrate, lanthanum chloride, yttrium chloride, and neodymium nitrate. In this invention, the range of selection for mixing conditions is relatively wide; preferably, the mixing temperature is 60-100℃ and the time is 2-6 hours. In this invention, conventionally defined washing and filtration methods are applicable and will not be elaborated further. In this invention, the range of selection for drying conditions is relatively wide. Preferably, the drying temperature is 50-200℃ and the time is 0.5-8 hours; more preferably, the drying temperature is 60-150℃ and the time is 0.5-6 hours. In this invention, the range of selection for calcination conditions is relatively wide. Preferably, the calcination temperature is 300-700℃ and the time is 0.5-8h, and more preferably the calcination temperature is 350-650℃ and the time is 0.5-6h.

[0062] The second aspect of the present invention provides a method for preparing a hydrodesulfurization catalyst, wherein the method includes: (1) mixing an inorganic heat-resistant matrix and / or its precursor with rare earth modified EWT structure molecules, molding, drying and calcining to obtain a support;

[0063] (2) The carrier from step (1) is impregnated with a solution containing the precursor of the active component and then dried and calcined;

[0064] The method also includes optionally introducing an adjuvant in step (1) and / or step (2);

[0065] The active component is selected from at least one group VIII metal element and at least one group VIB metal element;

[0066] The auxiliary agent is selected from at least one of fluorine, phosphorus and boron;

[0067] Based on the total amount of rare earth modified EWT structured molecular sieve, the content of rare earth elements in the rare earth modified EWT structured molecular sieve is 0.05-2.5% by weight.

[0068] In the rare earth-modified EWT structured molecular sieve, based on the total amount of rare earth-modified EWT structured molecular sieve, the total acid content is 0.25-0.5 mmol NH3·g. -1 Preferably, the concentration is 0.25-0.45 mmol NH3·g -1 ;

[0069] The ratio of Brønsted acid to Lønsted acid in the rare earth modified EWT molecular sieve is 0.1-1, preferably 0.15-0.6.

[0070] The preparation method of this invention is simple to operate, has a short process, and produces a catalyst with good stability. It can fully exert the synergistic effect between the acid centers of the molecular sieve and the active metal, promote the desulfurization reaction, and improve the desulfurization activity.

[0071] In a preferred embodiment, the amounts of the inorganic heat-resistant matrix, rare earth-modified EWT structured molecular sieve, Group VIII metal element, Group VIB metal element, and additives are such that, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is ​​20-80% by weight, the content of the rare earth-modified EWT structured molecular sieve is 5-40% by weight, the content of the Group VIII metal element (calculated as oxide) is 2-10% by weight, the content of the Group VIB metal element (calculated as oxide) is 10-40% by weight, and the content of the additives (calculated as oxide) is 0-8% by weight. More preferably, the amounts of the inorganic heat-resistant matrix, rare earth-modified EWT structured molecular sieve, Group VIII metal element, Group VIB metal element, and additives are such that, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is ​​30-70% by weight, the content of the rare earth-modified EWT structured molecular sieve is 5-30% by weight, the content of the Group VIII metal element (calculated as oxide) is 2-8% by weight, the content of the Group VIB metal element (calculated as oxide) is 10-30% by weight, and the content of the additives (calculated as oxide) is 0-7% by weight. This preferred embodiment helps to form a highly active hydrodesulfurization phase, with good catalyst stability and significantly improved desulfurization reaction activity.

[0072] In this invention, the types of inorganic heat-resistant matrices in step (1) have been described in the first aspect and will not be repeated here.

[0073] In this invention, the precursor of the inorganic heat-resistant matrix can be any substance that can be converted into an oxide matrix through subsequent calcination. Those skilled in the art can select the specific type of inorganic heat-resistant matrix, which will not be elaborated upon here. Preferably, the alumina precursor is selected from at least one of gibbsite, boehmite, diaspore, boehmite, and pseudoboehmite, and more preferably at least one of gibbsite, boehmite, and pseudoboehmite. This preferred embodiment can prepare a suitable and adjustable specific surface area and pore distribution, and the preparation process can control different calcination temperatures to obtain different crystal phases. It also possesses a certain degree of acidity, which is beneficial for improving catalytic activity.

[0074] In this invention, the types and sources of EWT structured molecular sieves have been described in the first aspect and will not be repeated here.

[0075] In a preferred embodiment, the rare earth element is selected from at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium, and is more preferably lanthanum and / or cerium. Modifying the EWT structured molecular sieve using the above-mentioned rare earth elements helps maintain or improve the structural stability of the molecular sieve and increases the total acidity of the molecular sieve.

[0076] In this invention, the content of each substance in the rare earth-modified EWT structured molecular sieve is not specifically limited. Preferably, based on the total amount of rare earth-modified EWT structured molecular sieve, the content of EWT structured molecular sieve is 97.95-99.9% by weight, the content of lanthanum is 0.05-1.25% by weight, and the content of cerium is 0.05-1.25% by weight; more preferably, based on the total amount of rare earth-modified EWT structured molecular sieve, the content of EWT structured molecular sieve is 98-99.9% by weight, the content of lanthanum is 0.05-1% by weight, and the content of cerium is 0.05-1% by weight. The advantage of this preferred embodiment is that it helps to increase the total acid content and improve the strong B / L acid ratio while maintaining the stability of the molecular sieve framework.

[0077] In this invention, the rare earth modified EWT structured molecular sieve is preferably prepared by ion exchange method. The preparation method has been described in the first aspect and will not be repeated here.

[0078] In this invention, there is no specific limitation on the molding method in step (1). Molding methods conventionally defined in the art are applicable to this invention. For example, they can be obtained by pressing, rolling, extruding, etc. Specifically, the molding can be obtained by the following method: The molding includes mixing an inorganic heat-resistant matrix and / or its precursor with rare earth modified EWT structural molecules, optionally an auxiliary precursor, and an extrusion aid and / or sol, and then extruding the mixture.

[0079] In this invention, there are no specific limitations on the types and amounts of extrusion aids and solvents. Those skilled in the art can select the types and amounts of extrusion aids and solvents within a reasonable range based on the specific circumstances of the extrusion molding. Preferably, the extrusion aid is selected from at least one of guar gum powder, dextrin, and methylcellulose. Preferably, the solvent is selected from at least one of nitric acid, acetic acid, and citric acid.

[0080] In a preferred embodiment, the amount of the extrusion aid is 0-6% by weight and the amount of the adhesive solvent is 0-5% by weight, based on the weight of the catalyst.

[0081] In this invention, the drying conditions in step (1) are selected within a wide range. Preferably, the drying temperature is 100-200℃ and the drying time is 2-12h.

[0082] In this invention, the range of selection for the calcination conditions in step (1) is relatively wide. Preferably, the calcination temperature is 350-650℃ and the time is 2-6h, and more preferably the temperature is 400-600℃ and the time is 3-5h.

[0083] In this invention, there is no particular limitation on the diameter of the carrier. Preferably, the equivalent diameter of the carrier is 1-4 mm, and more preferably 1.2-3.6 mm.

[0084] In this invention, there is no particular limitation on the shape of the carrier. Preferably, the carrier is cylindrical, clover-shaped, four-leaf clover-shaped, butterfly-shaped, or honeycomb-shaped.

[0085] In a preferred embodiment, the active component is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium, and platinum, and at least one of chromium, molybdenum, and tungsten, more preferably molybdenum and / or tungsten, and cobalt and / or nickel. This preferred embodiment is advantageous for giving the catalyst higher hydrodesulfurization activity and reaction stability.

[0086] In this invention, the active component is introduced in step (2) via an active component precursor. Active component precursors conventionally defined in the art are all applicable to this invention. Preferably, the active component precursor is selected from soluble salts of each active component. More preferably, the active component precursor is selected from at least one of cobalt nitrate, basic cobalt carbonate, cobalt acetate, cobalt sulfate, nickel nitrate, basic nickel carbonate, nickel acetate, and nickel sulfate, as well as at least one of ammonium heptamolybdate, ammonium molybdate, ammonium phosphomolybdate, molybdenum trioxide, ammonium metatungstate, and ethyl metatungstate.

[0087] In this invention, the active component can be introduced into the support using methods conventionally defined in the art, such as impregnation. Specifically, this invention employs the following method: a solution containing precursors of Group VIII and Group VIB metal elements is contacted with the support, followed by drying and calcination. In this invention, there is no specific limitation on the order of introduction of the Group VIII and Group VIB metal elements. The precursors of the Group VIII and Group VIB metal elements can be separately prepared into solutions and then contacted with the support, or the precursors of the Group VIII and Group VIB metal elements can be prepared into a mixed solution and then mixed with the support, followed by drying and calcination. Preferably, the precursors of the Group VIII and Group VIB metal elements are prepared into a mixed solution, mixed with the support, and then dried and calcined.

[0088] In this invention, the range of drying conditions in step (2) is relatively wide. Preferably, the drying temperature is 80-350℃ and the time is 1-24h, and more preferably the temperature is 100-250℃ and the time is 2-12h.

[0089] In this invention, the range of selection for the calcination conditions in step (2) is relatively wide. Preferably, the calcination temperature is 350-550℃ and the time is 1-8h; more preferably, the calcination temperature is 400-500℃ and the time is 2-7h. This preferred embodiment facilitates the full conversion of the active component precursor into the active component and its relatively uniform dispersion on the matrix, resulting in higher activity and stability of the catalyst.

[0090] In this invention, there is no particular limitation on the method of introducing the additives. They can be introduced by ion exchange, impregnation or coprecipitation, with impregnation being the preferred method.

[0091] In this invention, there is no particular limitation on the timing of introducing the additive. For example, it can be introduced in step (1) by mixing the solution containing the additive precursor with the rare earth modified EWT molecular sieve, molding, and calcining; or it can be introduced in step (2) by mixing the solution containing the additive precursor with the solution containing the active component precursor to prepare a mixed solution, then contacting it with the carrier and drying and calcining it. Preferably, it is introduced in step (2). The conditions for mixing and molding and calcining in step (1) and the conditions for drying and calcining in step (2) have been described above and will not be repeated here.

[0092] In this invention, there is no particular limitation on the type of precursor for the adjuvant; precursors conventionally defined in the art are all applicable to this invention. Preferably, the precursor for phosphorus is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and hypophosphoric acid; the precursor for fluorine is selected from at least one of fluorosilicic acid, ammonium fluoride, ammonium fluorosilicate, and ammonium fluoroborate; and the precursor for boron is selected from at least one of boric acid, borax, boron trifluoride, and potassium pentaborate.

[0093] In this invention, there is no specific limitation on the concentration of the precursor solution containing the auxiliary agent; those skilled in the art can select it according to actual needs. Preferably, the solid content of the precursor solution containing the auxiliary agent is 20-70% by weight.

[0094] The third aspect of this invention provides the application of the hydrodesulfurization catalyst described in the first aspect in a hydrodesulfurization reaction containing sterically hindered molecular feedstock.

[0095] In this invention, preferably, the sterically hindered molecular raw material refers to a sulfur-containing compound of the dibenzothiophene class containing alkyl substitution, preferably a diesel fuel of the dibenzothiophene class containing alkyl substituents at the 4 and 6 positions, more preferably 4-methyldibenzothiophene and / or 4,6-dimethyldibenzothiophene, even more preferably 4,6-dimethyldibenzothiophene, and even more preferably n-decane raw material with a content of 0.33-0.66% by weight.

[0096] In a preferred embodiment, the hydrodesulfurization reaction conditions include: a temperature of 200-500°C, a pressure of 2-10 MPa, and a liquid hourly space velocity of 0.1-100 h⁻¹. -1 The hydrogen-to-oil volume ratio is 100-5000, more preferably at a temperature of 200-400℃, a pressure of 3-8 MPa, and a liquid hourly space velocity of 0.2-80 h⁻¹. -1 The hydrogen-to-oil volume ratio is 200-1000.

[0097] In a preferred embodiment, the catalyst provided by the present invention needs to be sulfided in a hydrogen-containing atmosphere using sulfur, hydrogen sulfide, or sulfur-containing raw materials before use. The sulfidation method is not particularly limited in the present invention and can be either dry sulfidation or wet sulfidation.

[0098] In this invention, there are no particular limitations on the sulfidation conditions. Preferably, the sulfidation reaction temperature is 120-400℃, the time is 0.5-10h, and the volume hourly space velocity is 0.5-200h. -1 The hydrogen-to-oil volume ratio is 100-2000, and the hydrogen partial pressure is 0.1-10 MPa.

[0099] In a preferred embodiment, the vulcanization process is performed either in situ vulcanization within a vulcanization reactor or vulcanization outside the vulcanization reactor.

[0100] The present invention will be described in detail below through examples. Unless otherwise specified, all reagents used in the present invention are analytical grade reagents.

[0101] Preparation Examples 1-7 and Comparative Preparation Examples 1-3 are used to illustrate the preparation of the support.

[0102] In the preparation example, template agent X1 is a 1,1,6,6-tetramethyl-1,6-diazadodecyl-1,6-diquaternary ammonium base, and template agent X2 is a 1,1,6,6-tetramethyl-1,6-diazadodecyl-1,6-diquaternary ammonium base.

[0103] Preparation Example 1

[0104] An initial gel mixture containing coarse silica gel (produced by Qingdao Ocean Chemical Co., Ltd., industrial grade, SiO2 content 98% by weight), aluminum nitrate, template agent X1, deionized water, and sodium hydroxide was prepared. The molar ratio of the reactants was SiO2:Al2O3:X1:H2O:NaOH = 1:0.015:0.15:10:0.1. The prepared initial gel mixture was placed in a 45 mL steel autoclave with a polytetrafluoroethylene liner, sealed, and then placed in a rotary oven (20 rpm) for crystallization. The reaction was carried out at 120℃ for 1 day, and then the temperature was increased to 150℃ for 4 days. After crystallization, the molecular sieve slurry was subjected to ammonium exchange at 75℃ for 4 hours, washed with deionized water, filtered, dried at 120℃ for 5 hours, and calcined at 550℃ for 5 hours to obtain the EWT structured molecular sieve (numbered E-1).

[0105] 0.12 g of cerium nitrate was dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of E-1 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number CE-1, sodium oxide content 0.1 wt%, dry basis 0.83). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0106] 32.0 g of rare earth modified EWT structured molecular sieve was mixed with 214.3 g of pseudoboehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.6 g of guar gum powder, and 172.9 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into butterfly-shaped strips with an equivalent outer diameter of 1.5 mm, dried at 120 °C for 4 hours, and calcined at 580 °C for 3 hours to prepare the support ACE-1.

[0107] Preparation Example 2

[0108] EWT structured molecular sieves, designated E-2, were synthesized using the same method as in Preparation Example 1.

[0109] 0.23 g of lanthanum nitrate was dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of E-2 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (No. LE-2, sodium oxide content 0.1 wt%, dry basis 0.88). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0110] 30.2 g of rare earth modified EWT molecular sieve was mixed with 214.3 g of PB powder (0.7 g dry basis), 4.5 g of guar gum powder, and 171.2 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm. The strip was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ALE-2.

[0111] Preparation Example 3

[0112] EWT structured molecular sieves were synthesized using the same method as in Preparation Example 1, except that X2 was used as the template agent, and the resulting molecular sieve was designated E-3.

[0113] 1.16 g of cerium nitrate was dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of E-3 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number CE-3, sodium oxide content 0.1 wt%, dry basis 0.81). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0114] 32.6 g of rare earth modified EWT molecular sieve was mixed with 214.3 g of PB powder (0.7 g dry basis), 4.6 g of guar gum powder, and 173.5 mL of an aqueous solution containing 3.7 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm. The strip was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ACE-3.

[0115] Preparation Example 4

[0116] EWT structured molecular sieves, designated E-4, were synthesized using the same method as in Preparation Example 1.

[0117] 0.23 g of lanthanum nitrate was dissolved in 48 mL of deionized water to prepare an impregnation solution. The impregnation solution was mixed with 50 g of E-4 molecular sieve sample at 30 °C and allowed to stand for 3 hours. Then, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number LE-4, sodium oxide content 0.1 wt%, dry basis 0.87). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0118] 30.3 g of rare earth modified EWT molecular sieve was mixed with 214.3 g of PB powder (0.7 g dry basis), 4.5 g of guar gum powder, and 171.3 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm. The strip was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ALE-4.

[0119] Preparation Example 5

[0120] EWT structured molecular sieves were synthesized using the same method as in Preparation Example 1, except that X2 was used as the template agent, and the resulting molecular sieve was numbered E-5.

[0121] 0.12 g of cerium nitrate and 0.12 g of lanthanum nitrate were dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of E-5 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number CLE-5, sodium oxide content 0.1 wt%, dry basis 0.89). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0122] 29.7 g of rare earth modified EWT molecular sieve was mixed with 214.3 g of PB powder (0.7 g dry basis), 4.5 g of guar gum powder, and 173.5 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm. The strip was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ACLE-5.

[0123] Preparation Example 6

[0124] EWT structured molecular sieves, designated E-6, were synthesized using the same method as in Preparation Example 1.

[0125] 0.23 g of neodymium nitrate was dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of E-6 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number NE-6, sodium oxide content 0.1 wt%, dry basis 0.82). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0126] 40.4 g of rare earth modified EWT molecular sieve was mixed with 142.9 g of PB powder (0.7 g dry basis), 4.2 g of guar gum powder, and 140.4 mL of an aqueous solution containing 3.5 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm. The strip was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ANE-6.

[0127] Preparation Example 7

[0128] EWT structured molecular sieves, designated E-7, were synthesized using the same method as in Preparation Example 1.

[0129] 0.23 g of cerium nitrate was dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of E-7 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number CE-7, sodium oxide content 0.1 wt%, dry basis 0.83). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0130] 32.0 g of rare earth modified EWT molecular sieve was mixed with 214.3 g of PB powder (0.7 g dry basis), 4.6 g of guar gum powder, 172.9 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid and 5.4 g of phosphoric acid (a product of Beijing Chemical Plant, 85% by weight). The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm, dried at 120 °C for 4 hours, and calcined at 580 °C for 3 hours to prepare the carrier ACE-7.

[0131] Comparative Preparation Example 1

[0132] Take 214.3 g of PB powder (0.7 g dry basis) and mix it with 3.8 g of guar gum powder and 142.5 mL of aqueous solution containing 3.0 mL of analytical grade (65-68% by weight) nitric acid. Extrude the mixture into a butterfly-shaped strip with an equivalent diameter of 1.5 mm, dry it at 120 °C for 4 hours, and calcine it at 580 °C for 3 hours to prepare carrier A.

[0133] Comparative Preparation Example 2

[0134] EWT-structured molecular sieves (DE-2, sodium oxide content 0.1%, dry basis 0.83%) were synthesized using the same method as in Preparation Example 1. The structural properties of the molecular sieves are shown in Table 1.

[0135] 32.1 g of EWT structured molecular sieve, 214.3 g of PB powder (0.7 g dry basis), 4.6 g of guar gum powder, and 172.9 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid were mixed and extruded into butterfly-shaped strips with an equivalent diameter of 1.5 mm. The mixture was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ADE-2.

[0136] Comparative preparation example 3

[0137] EWT structured molecular sieves, designated DE-3, were synthesized using the same method as in Preparation Example 1.

[0138] 3.49 g of cerium nitrate was dissolved in 500 mL of deionized water to prepare an ion exchange solution. The ion exchange solution was mixed with 50 g of DE-3 molecular sieve sample at 80 °C for 3 hours. After filtration and washing, the sample was dried and calcined at 120 °C and 550 °C for 3 hours respectively to obtain rare earth modified EWT structure molecular sieve sample (number CDE-3, sodium oxide content 0.1 wt%, dry basis 0.86). The structural properties of rare earth modified EWT structure molecular sieve are shown in Table 1, and the content of modified rare earth elements is shown in Table 2.

[0139] 30.6 g of rare earth modified EWT molecular sieve was mixed with 214.3 g of PB powder (0.7 g dry basis), 4.5 g of guar gum powder, and 171.6 mL of an aqueous solution containing 3.6 mL of analytical grade (65-68% by weight) nitric acid. The mixture was extruded into a butterfly-shaped strip with an equivalent diameter of 1.5 mm. The strip was dried at 120 °C for 4 hours and calcined at 580 °C for 3 hours to prepare the carrier ACDE-3.

[0140] Table 1

[0141]

[0142]

[0143] Note: In Preparation Examples 1-7 in Table 1, the total acid content is based on the total amount of rare earth modified EWT structured molecular sieves; in Comparative Preparation Example 2, the total acid content is based on the total amount of EWT structured molecular sieves; and in Comparative Example 3, the total acid content is based on the total amount of rare earth modified EWT structured molecular sieves.

[0144] Table 1 shows that after rare earth modification, the silicon-to-aluminum atomic ratio of the EWT molecular sieve decreased slightly, the proportion of non-framework aluminum increased, and the specific surface area and pore volume decreased slightly, indicating that rare earth modification had little effect on the molecular sieve framework and the structure of the molecular sieve remained stable. Before and after rare earth modification, the B / L acid ratio of the EWT molecular sieve was less than 1, indicating that its acid centers still mainly existed in the form of Lipoic acid, with a low proportion of Benzoic acid. However, after rare earth modification, the total acid content of the EWT molecular sieve increased; the strong B / L acid ratio (at 350℃) significantly increased, which helps more Benzoic acid centers participate in the reaction and promotes the conversion of sulfur-containing compounds.

[0145] Table 2

[0146]

[0147]

[0148] Note: In Preparation Examples 1-7 in Table 2, the content of each substance is based on the total amount of rare earth modified EWT structured molecular sieves; in Comparative Preparation Example 2, the content of each substance is based on the total amount of EWT structured molecular sieves; in Comparative Preparation Example 3, the content of each substance is based on the total amount of rare earth modified EWT structured molecular sieves.

[0149] The examples and comparative examples are used to illustrate catalyst preparation.

[0150] Example 1

[0151] 100 g of ACE-1 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-1. The contents of each substance in the catalyst are shown in Table 3.

[0152] Example 2

[0153] 100 g of ALE-2 support was impregnated with 76 mL of an aqueous solution containing 43.6 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.5 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 10.9 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-2. The contents of each substance in the catalyst are shown in Table 3.

[0154] Example 3

[0155] 100 g of ACE-3 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-3. The contents of each substance in the catalyst are shown in Table 3.

[0156] Example 4

[0157] 100 g of ALE-4 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-4. The contents of each substance in the catalyst are shown in Table 3.

[0158] Example 5

[0159] 100 g of ACLE-5 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-5. The contents of each substance in the catalyst are shown in Table 3.

[0160] Example 6

[0161] 100 g of ANE-6 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-6. The contents of each substance in the catalyst are shown in Table 3.

[0162] Example 7

[0163] 100 g of ACE-7 support was impregnated with 70 mL of an aqueous solution containing 36.3 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.1 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 6.0 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst C-7. The contents of each substance in the catalyst are shown in Table 3.

[0164] Comparative Example 1

[0165] 100 g of carrier A was impregnated with a 70 mL aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The mixture was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst D-1. The contents of each substance in the catalyst are shown in Table 3.

[0166] Comparative Example 2

[0167] 100 g of ADE-2 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst D-2. The contents of each substance in the catalyst are shown in Table 3.

[0168] Comparative Example 3

[0169] 100 g of ACDE-3 support was impregnated with 70 mL of an aqueous solution containing 36.9 g of molybdenum trioxide (Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (based on cobalt oxide, produced by Sinopharm Chemical Reagent Co., Ltd.), and 9.1 g of phosphoric acid (produced by Beijing Chemical Plant, with a phosphoric acid content of 85% by weight). The solution was dried at 120 °C for 4 hours and calcined at 400 °C for 3 hours to obtain catalyst D-3. The contents of each substance in the catalyst are shown in Table 3.

[0170] Table 3

[0171]

[0172] Performance testing

[0173] The catalysts from Examples 1-7 and Comparative Examples 1-3 were crushed into particles of 0.25-0.38 mm. 0.15 g of the catalyst sample was weighed and mixed evenly with 1 g of quartz sand of the same particle size, then loaded into a fixed-bed reactor. Before the reaction, the catalyst underwent pre-sulfurization treatment under the following conditions: a 5% CS2 cyclohexane solution as the sulfiding oil, a hydrogen partial pressure of 4.0 MPa, a temperature of 360°C, a sulfidation time of 4 h, and a hydrogen-to-oil volume ratio of 900.

[0174] After pre-sulfurization, the reaction oil was switched to a 0.45 wt% n-decane solution of 4,6-DMDBT. The reaction conditions were: hydrogen partial pressure of 4.0 MPa, reaction temperature of 300℃, reaction oil flow rate of 0.2 mL / min, hydrogen-to-oil volume ratio of 500, and samples were taken for analysis after stabilization for 2 hours.

[0175] The conversion rate, selectivity of the direct desulfurization pathway, desulfurization rate, total activity of the desulfurization reaction, direct desulfurization activity, and hydrogen consumption of 4,6-DMDBT were calculated using the following formulas, and the results are shown in Table 4.

[0176] If we define the direct desulfurization activity of the catalyst prepared in Comparative Example 1 as 100, we can calculate the relative direct desulfurization activities of the catalysts in other test examples, as shown in Table 4.

[0177]

[0178]

[0179]

[0180]

[0181] Direct desulfurization activity = Total desulfurization reaction activity × Selectivity of the direct desulfurization pathway

[0182]

[0183] Table 4

[0184]

[0185]

[0186] The results show that the conversion rate and desulfurization rate of the catalyst containing rare earth-modified EWT molecular sieve in the examples are higher than those of the catalyst without molecular sieve. The catalyst also exhibits higher selectivity for the direct desulfurization pathway and significantly improved direct desulfurization activity. Regarding hydrogen consumption, the addition of rare earth-modified EWT molecular sieve significantly reduces hydrogen consumption in the desulfurization reaction and improves hydrogen utilization efficiency during the desulfurization process. All these data indicate that the catalyst containing rare earth-modified EWT molecular sieve provided in this invention has good application prospects in the ultra-deep hydrodesulfurization process of diesel fuel.

[0187] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A hydrodesulfurization catalyst, wherein, The catalyst includes a support, an active component supported on the support, and optional additives; The carrier comprises an inorganic heat-resistant matrix and a rare-earth modified EWT structured molecular sieve; wherein, based on the total amount of rare-earth modified EWT structured molecular sieve, the content of rare earth elements in the rare-earth modified EWT structured molecular sieve is 0.05-0.9% by weight; wherein, based on the total amount of rare-earth modified EWT structured molecular sieve, the total acidity in the rare-earth modified EWT structured molecular sieve is 0.25-0.45 mmol NH3. g -1 The rare earth-modified EWT structured molecular sieve has a Brønsted acid / Lønsted acid content ratio of 0.1-1 and a specific surface area of ​​500-650 m². 2 / g, pore volume 0.25-0.35cm³ 3 / g; Wherein, in the rare earth modified EWT structure molecular sieve, the EWT structure molecular sieve is EMM-23; wherein, the active component is selected from at least one of Group VIII metal elements and at least one of Group VIB metal elements; The auxiliary agent is selected from at least one of fluorine, phosphorus and boron; Based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is ​​30-70% by weight, the content of the rare earth modified EWT structure molecular sieve is 5-30% by weight, the content of the Group VIII metal element (calculated as oxide) is 2-8% by weight, the content of the Group VIB metal element (calculated as oxide) is 10-30% by weight, and the content of the additive (calculated as oxide) is 0-7% by weight.

2. The catalyst according to claim 1, wherein, The inorganic heat-resistant matrix is ​​selected from at least one of alumina, silicon dioxide, titanium dioxide, magnesium oxide, alumina-magnesium oxide, silicon dioxide-alumina, silicon dioxide-magnesium oxide, silicon dioxide-zirconium oxide, silicon dioxide-thorium oxide, silicon dioxide-beryllium oxide, silicon dioxide-titanium oxide, silicon dioxide-alumina-thorium oxide, silicon dioxide-alumina-titanium oxide, silicon dioxide-alumina-magnesium oxide, silicon dioxide-alumina-zirconium oxide, phosphorus oxide-alumina, phosphorus oxide-alumina-alumina, and natural zeolite.

3. The catalyst according to claim 2, wherein, The inorganic heat-resistant matrix is ​​alumina.

4. The catalyst according to any one of claims 1-3, wherein, The rare earth element is selected from at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium.

5. The catalyst according to claim 4, wherein, The rare earth element is lanthanum and / or cerium.

6. The catalyst according to claim 5, wherein, Based on the total amount of rare earth modified EWT structured molecular sieve, the content of EWT structured molecular sieve in the rare earth modified EWT structured molecular sieve is 97.95-99.9% by weight, the content of lanthanum is 0.05-1.25% by weight, and the content of cerium is 0.05-1.25% by weight.

7. The catalyst according to any one of claims 1-3, wherein, The modified EWT structured molecular sieve has a Brønsted acid / Lønsted acid content ratio of 0.15-0.

6.

8. The catalyst according to any one of claims 1-3, wherein, The rare earth modified EWT structured molecular sieve has a silicon-to-aluminum atomic ratio of 10-50 and a framework aluminum / non-framework aluminum ratio of 1-6.

9. The catalyst according to claim 8, wherein, The rare earth modified EWT structure molecular sieve has a silicon-to-aluminum atomic ratio of 30-50 and a framework aluminum / non-framework aluminum ratio of 1-3.

10. The catalyst according to any one of claims 1-3, wherein, The method for preparing the rare earth modified EWT structured molecular sieve includes: introducing rare earth elements into the EWT structured molecular sieve for modification by at least one of ion exchange, impregnation and precipitation methods.

11. The catalyst according to claim 10, wherein, The solution containing rare earth element precursors is ion exchanged with EWT structured molecular sieves using an ion exchange method, followed by drying and calcination.

12. The catalyst according to claim 11, wherein, The rare earth element precursor is selected from at least one of nitrates, sulfates, chlorides, phosphates, and carbonates.

13. The catalyst according to claim 11, wherein, The drying temperature is 50-200℃, and the time is 0.5-8h.

14. The catalyst according to claim 11, wherein, The roasting temperature is 300-700℃, and the time is 0.5-8h.

15. A method for preparing the hydrodesulfurization catalyst according to claim 1, wherein, The method includes: (1) An inorganic heat-resistant matrix and / or its precursor are mixed with rare earth modified EWT structure molecular sieves, molded, dried and calcined to obtain a support; (2) The carrier from step (1) is impregnated with a solution containing the precursor of the active component and then dried and calcined; The method also includes optionally introducing an adjuvant in step (1) and / or step (2).

16. The preparation method according to claim 15, wherein, In step (1), the inorganic heat-resistant matrix is ​​selected from at least one of alumina, silicon oxide, titanium oxide, magnesium oxide, alumina-magnesium oxide, silicon oxide-alumina, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thorium oxide, silicon oxide-beryllium oxide, silicon oxide-titanium oxide, silicon oxide-alumina-thorium oxide, silicon oxide-alumina-titanium oxide, silicon oxide-alumina-magnesium oxide, silicon oxide-alumina-zirconium oxide, phosphorus oxide-alumina, phosphorus oxide-alumina-alumina and natural zeolite.

17. The preparation method according to claim 16, wherein, In step (1), the inorganic heat-resistant matrix is ​​alumina.

18. The preparation method according to claim 17, wherein, In step (1), the alumina precursor is selected from at least one of gibbsite, boehmite, diaspore, boehmite, and pseudoboehmite.

19. The preparation method according to claim 15, wherein, In step (1), the rare earth element is selected from at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium.

20. The preparation method according to claim 19, wherein, In step (1), the rare earth element is lanthanum and / or cerium.

21. The preparation method according to claim 15, wherein, In step (1), based on the total amount of rare earth modified EWT structure molecular sieve, the content of EWT structure molecular sieve in the rare earth modified EWT structure molecular sieve is 97.95-99.9% by weight, the content of lanthanum is 0.05-1.25% by weight, and the content of cerium is 0.05-1.25% by weight.

22. The preparation method according to claim 15, wherein, In step (1), the preparation method of the rare earth modified EWT structure molecular sieve includes: introducing rare earth elements into the EWT structure molecular sieve for modification by at least one of ion exchange method, impregnation method and precipitation method.

23. The preparation method according to claim 22, wherein, In step (1), the solution containing rare earth element precursors is ion exchanged with EWT structure molecular sieve by ion exchange method, and then dried and calcined.

24. The preparation method according to claim 15, wherein, In step (1), the roasting temperature is 350-650℃ and the time is 2-6h.

25. The preparation method according to claim 24, wherein, In step (1), the roasting temperature is 400-600℃ and the time is 3-5h.

26. The preparation method according to any one of claims 15-25, wherein, In step (2), the active component is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum, and at least one of chromium, molybdenum and tungsten.

27. The preparation method according to claim 26, wherein, In step (2), the active components are molybdenum and / or tungsten, as well as cobalt and / or nickel.

28. The preparation method according to any one of claims 15-25, wherein, In step (2), the drying temperature is 80-350℃ and the time is 1-24h.

29. The preparation method according to claim 28, wherein, In step (2), the drying temperature is 100-250℃ and the time is 2-12h.

30. The preparation method according to any one of claims 15-25, wherein, In step (2), the roasting temperature is 350-550℃ and the time is 1-8h.

31. The preparation method according to claim 30, wherein, In step (2), the roasting temperature is 400-500℃ and the time is 2-7h.

32. The use of the hydrodesulfurization catalyst according to any one of claims 1-14 in the hydrodesulfurization reaction containing sterically hindered molecular feedstock.

Citation Information

Patent Citations

  • Hydrogenation catalyst and preparation method thereof

    CN103143365A

  • Carrier of hydrogen desulfurization catalyst and preparation method and catalyst prepared by preparation method

    CN105772109A

  • Preparation method of ultra-deep desulfurization catalyst

    CN107694583A

  • Molecular sieve, production method and applications thereof

    CN108238610A

  • Method for preparing tert-butyl glyceryl ether by glycerol etherification

    CN109422627A